Kajian Pemanfaatan Daging Ikan Kembung (Rastrelliger Spp) Sebagai Bahan Penyedap Rasa Alami Non MSG Dengan Pendekatan Bioekonomi Perikanan - Teni Novianti (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2020)
Currently, most food products circulating in the community are processed using additives, both natural and synthetic. One of the potential food ingredients that can be used as a natural flavor enhancer from fishery raw materials is long jawed mackerel (Rastrelliger spp). The purpose of this study was to studied preliminary research on the use of long jawed mackerel as an alternative material for natural non-MSG flavorings to replace synthetic flavors with a fisheries bioeconomic approach. The procedure in this study consisted of several steps, namely the manufacture of natural flavorings from long jawed mackerel, calculation of fish yield, analysis of water content and salt content (NaCl). Based on the research results, the processing stages of non-MSG natural flavoring made from long jawed mackerel fish include the process of selecting raw materials, washing I, filling, washing II, refining I, weighing I, drying, refining II, sifting, weighing II and packaging. The amount of long jawed mackerel yield that can be used as the main raw material for the manufacture of natural non-MSG flavorings is 53% with the final weight of flavoring powder produced is 440 grams. The chemical analysis test of the long jawed mackerel flavoring was carried out 2 repetitions and the results of the water content test were 5.35% (has not met the SNI quality requirements), while the analysis of salt content (NaCl) on the long jawed mackerel flavoring has met the SNI quality requirements with a value of 12.09%. Bioeconomic analysis of fisheries is by calculating production costs and depreciation costs incurred during the processing of flavorings from long jawed mackerel. Based on the analysis, one production time produces 88 pcs of flavoring fish meat with a cost of production of Rp. 1,496 per pcs.